A monetary and fiscal history of the united states, 1961-2021 - Blinder, Alan S. (New Jersey Princeton University Press, 2022)
In this book, Alan Blinder, one of the world$1 (Bs most influential economists and one of the field$1 (Bs best writers, draws on his deep firsthand experience to provide an authoritative account of sixty years of monetary and fiscal policy in the United States. Spanning twelve presidents, from John F. Kennedy to Joe Biden, and eight Federal Reserve chairs, from William McChesney Martin to Jerome Powell, this is an insider$1 (Bs story of macroeconomic policy that hasn$1 (Bt been told before$1 (Bone that is a pleasure to read, and as interesting as it is important.s